Pengaruh Gaya Hidup, Citra Merek dan Kelompok Referensi terhadap Keputusan Pembelian (Studi Pada Konsumen Sepatu Adidas di Semarang) - Bhekti Irdhi Viatama; Alimuddin Rizal (Universitas Batanghari Jambi, 2023)
This study aims to test the influence of lifestyle, brand image and reference groups on the purchasing decisions of studies on consumers of Adidas shoes in Semarang. This research is a quantitative study. The sampling technique uses purposive sampling. The criteria in this study are people who have bought and used at least once, aged at least 17 years. The data collection technique uses a questionnaire with the filling out of 100 respondents. The instrument used to obtain variable data is measured on a likert scale. The tests in this study used validity tests with factor analysis, reliability tests using cronchbach's alpha, and further analyzed with multiple linear regression analysis. The results showed that lifestyle variables (X1), brand image (X2), and reference group (X3) had a partial or simultaneous positive effect on purchasing decisions on Adidas shoes in Semarang.